REPRESENTATION OF STUDENT BULLYING ACTS IN KOREAN DRAMA (ROLAND BARTHES SEMIOTIC ANALYSIS IN THE GLORY DRAMA SEASON 1) - Chandra, Cristin (Acta Diurna: Jurnal Ilmu Komunikasi, 2024)
This article presents the results of research on bullying acts in the Korean drama series The Glory Season 1 (2022). The drama depicts acts of revenge by victims of bullying during their teenage years. This research is qualitative and utilizes Roland Barthes’s semiotics method for analysis. The study results demonstrate that the acts of bullying perpetrated by individuals can be categorized into several types. Bullies will continue to harass victims until they are satisfied. Through this research it was also found that films can be an examples for the audience to take certain actions.